Upgrading the value chain of Indonesian Agricultural Sector: Review of Theory and Empirical Results (Jurnal Sosial Ekonomi Pertanian, 2023)
The value chain of the agricultural sector of developing countries, including Indonesia, is part of a global value-chain, especially for the value chain of plantation products that are traded globally (for example, coffee, cocoa, tea, and palm oil). Many researchers use a global value-chain perspective with a focus on evaluating the relationship between multinational companies (which are considered the main actors) and other actors (including producers and consumers) in international trade. However, the argument that developing countries need to have more control over global value-chains deserves attention. Therefore, this study aims to identify potential strategies for upgrading the value chain as a whole and in a more systematic manner; thereby strengthening its position and influence in global value-chains. The research objective is achieved by reviewing the literature specifically on the value chain, but also by expanding the review to literature on politics, economics and management. In addition, this research is also strengthened by the results of empirical research as 'cases' or 'examples' related to the proposed strategies. The results of the study indicate that upgrading the value chain is achieved through a combination of strategies, for example increasing product value added and improving chain governance. In addition, this study concludes that, in the era of the liberalized market, the role of the government should be more visible. The liberalized market does not always achieve an optimal equilibrium, and therefore the government must be able to correct it with relevant regulations and/or policies.
Keywords: agricultural sector; developing country; Indonesia; upgrading; value chain